Appropriate technology in third world development / edited by Pradip K. Ghosh (London, 1984)
The role of appropriate technology in developing the Third World is the focus of this volume. The use of such technology, research, selection, and sources of it, and its application within the framework of development policy are among the many aspects of appropriate technology explored and analyzed in these essays. A broad range of theoretical surveys and specific case studies are also provided.
Keywords: Appropriate technology